Internalization of Worship Values Based on Student Discipline Habits at MIN 2 Boyolali - Suparmi; Siti Rohimah (Didaktika: Jurnal Kependidikan, 2024)
This research aims to determine the internalization of religious values based on students' discipline habits. This research is a qualitative research. The subjects in this research were Islamic Religious Education Teachers, madrasa heads, student guardians and students of MIN 2 Boyolali. This research was conducted at MIN 2 Boyolali from October to December 2023. This data was obtained by observation, structured interviews, and documentation as well as relevant literature results. Data analysis uses the Miles and Huberman analysis model called interactive analysis. This analysis is divided into several stages: data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the habit of internalizing the values of worship is based on the habit of discipline through tahfidz, Friday prayers and midday prayers in congregation. Meanwhile, there are internal supporting factors, namely student interest, student awareness and students' innate characteristics, all of which support the internalization of religious values based on disciplined habits. And external factors in the form of environmental and community conditions. Meanwhile, the inhibiting factors are children's lazy habits, the influence of peers and busy parents, so that the internalization of religious values based on students' habituation of discipline is not effective.